Supervisor perception of virtual-based supervision development for physical education teachers - Yudha Munajat Saputra; Sandey Tantra Paramitha; Muhammad Gilang Ramadhan (JUARA : Jurnal Olahraga, 2022)
Objectives: The presence of modern technology today reaches all aspects of life, including teachers' supervision, developed through a touch of technology. One of them is the supervision of a teacher learning system for their students on a virtual basis. This study aimed to analyze the supervisor's perception of the need to develop a virtual-based supervision model that the researcher would create. The development of this supervision model is necessary because it is considered that currently, supervision has not been running optimally and effectively. Therefore, before the development of the supervision model, the researchers conducted a needs analysis. Methods: The method used was a qualitative research approach, with interviews and document studies as data collection techniques to gain what supervisors wanted and needed in increasing teacher supervision. The subjects of this study were the supervisors of education in West Java Province. Results: The results of this study found that supervisors need to develop a supervision model to increase the supervision of teachers. Of course, the supervisors agreed with the development of virtual-based supervision. So that supervision will be something needed by supervisors. Conclusions: Based on the need for optimization and the effectiveness of supervision, the supervisor's perception indicates that they strongly agree with this development.